Experiment of "No-Tillage" Farming System on the Volcanic Soils of Tropical Islands of Micronesia - Mohammad H. Golabi; S.A. El-Swaify; Clancy Iyekar (International Soil and Water Conservation Research, 2014)
The soils of southern Guam are formed from very deep; well-drained Saprolite derived from volcanic based tuff and tuff breccias. These soils suffer severe erosion as the result of rapid overland flow, wind and intensive rain events typical of southern Guam. An integrated approach to control the accelerated soil erosion was designed to include conservation tillage, crop rotation with leguminous plant, and residue management for soil surface cover. The objectives of this study are; 1) to evaluate the use of crop rotation and tillage management for increasing organic-matter content to improve the overall quality of these severely eroded soils, 2) to evaluate the effect of conservation practices on harvested yield and crop productivity of these eroded soils and, 3) to assess the effects of conservation techniques including no-tillage systems on water runoff and infiltration. This paper discusses the effect of conservation strategies and techniques on these severely eroded soils of southern Guam.